Controlled synthesis of O-glycopolypeptide polymers and their molecular recognition by lectins - Pati, Debasis; Shaikh, Ashif Y.; Das, Soumen; Nareddy, Pavan Kumar; Swamy, Musti J.; Hotha, Srinivas; Sen Gupta, Sayam (Biomacromolecules, 2012)
The facile synthesis of high molecular weight water-soluble O-glycopolypeptide polymers by the ring-opening polymerization of their corresponding N-carboxyanhydride (NCA) in very high yield (overall yield > 70%) is reported. The per-acetylated-O-glycosylated lysine-NCA monomers, synthesized using stable glycosyl donors and a commercially available protected amino acid in very high yield, was polymerized using commercially available amine initiators. The synthesized water-soluble glycopolypeptides were found to be alpha-helical in aqueous solution. However, we were able to control the secondary conformation of the glycopolypeptides (alpha-helix vs nonhelical structures) by polymerizing raceznic amino acid glyco NCAs. We have also investigated the binding of the glycopolypeptide poly(alpha-manno-O-lys) with the lectin Con-A using precipitation and hemagglutination assays as well as by isothermal titration calorimetry (ITC). The ITC results clearly show that the binding process is enthalpy driven for both alpha-helical and nonhelical structures, with negative entropic contribution. Binding stoichiometry for the glycopolypeptide poly(alpha-manno-O-lys) having a nonhelical structure was slightly higher as compared to the corresponding polypeptide which adopted an alpha-helical structure.

Polyproline fold-In imparting kinetic stability to an alkaline serine endopeptidase - Rohamare, Sonali B.; Dixit, Vaishali; Nareddy, Pavan Kumar; Sivaramakrishna, D.; Swamy, Musti J.; Gaikwad, Sushama M. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2013)
Polyproline II (PPII) fold, an unusual structural element was detected in the serine protease from Nocardiopsis sp. NCIM 5124 (NprotI) based on far UV circular dichroism spectrum, structural transitions of the enzyme in presence of GdnHCl and a distinct isodichroic point in chemical and thermal denaturation. The functional activity and conformational transitions of the enzyme were studied under various denaturing conditions. Enzymatic activity of NprotI was stable in the vicinity of GdnHCl upto 6.0 M concentration, organic solvents viz, methanol, ethanol, propanol (all 90% v/v), acetonitrile (75% v/v) and proteases such as trypsin, chymottypsin and proteinase K (NprotI:protease 10:1). NprotI seems to be a kinetically stable protease with a high energy barrier between folded and unfolded states. Also, an enhancement in the activity of the enzyme was observed in 1 M GdnHCl upto 8 h, in organic solvents (75% v/v) for 72 h and in presence of proteolytic enzymes. The polyproline fold remained unaltered or became more prominent under the above mentioned conditions. However, it diminished gradually during thermal denaturation above 60 degrees C. Thermal transition studies by differential scanning calorimetry (DSC) showed scan rate dependence as well as irreversibility of denaturation, the properties characteristic of kinetically stable proteins. This is the first report of PPII helix being the global conformation of a non structural protein, an alkaline serine protease, from a microbial source, imparting kinetic stability to the protein. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Conformation; differential scanning calorimetry; Kinetic stability; Nocardiopsis sp.; Polyproline fold; Serine protease

Acid stability of the kinetically stable alkaline serine protease possessing polyproline II fold - Rohamare, Sonali; Javdekar, Vaishali; Dalal, Sayli A.; Nareddy, Pavan Kumar; Swamy, Musti J.; Gaikwad, Sushama M. (Protein Journal, 2015)
The kinetically stable alkaline serine protease from Nocardiopsis sp.; NprotI, possessing polyproline II fold (PPII) was characterized for its pH stability using proteolytic assay, fluorescence and Circular Dichroism (CD) spectroscopy, and Differential Scanning Calorimetry (DSC). NprotI was found to be functionally stable when incubated at pH 1.0, even after 24 h, while after incubation at pH 10.0, drastic loss in the activity was observed. The enzyme showed enhanced activity after incubation at pH 1.0 and 3.0, at higher temperature (50-60 A degrees C). NprotI maintained the overall PPII fold in broad pH range as seen using far UV CD spectroscopy. The PPII fold of NprotI incubated at pH 1.0 remained fairly intact up to 70 A degrees C. Based on the isodichroic point and T-m values revealed by secondary structural transitions, different modes of thermal denaturation at pH 1.0, 5.0 and 10.0 were observed. DSC studies of NprotI incubated at acidic pH (pH 1.0-5.0) showed T-m values in the range of 74-76 A degrees C while significant decrease in T-m (63.8 A degrees C) was observed at pH 10.0. NprotI could be chemically denatured at pH 5.0 (stability pH) only with guanidine thiocynate. NprotI can be classified as type III protein among the three acid denatured states. Acid tolerant and thermostable NprotI can serve as a potential candidate for biotechnological applications.
Keywords: Acid stability; DSC; Kinetic stability; Polyproline fold; Protease; Thermal unfolding